Major General Oldřich Španiel: The Unofficial Czechoslovak Military Attaché in the United States (1939–1941) - Jiránek, Tomáš (My University, 2016)
During the World War II, the Czechoslovak exile authorities were building military units, which should have supported the effort of the anti-fascist coalition. The study deals with the ways of the work of Oldřich Španiel in the USA, cooperation with local authorities, the relations among compatriots and recruitment of soldiers.
Plukovník gšt. Oldřich Španiel - neoficiální československý vojenský atašé v USA (1939-1941).
Keywords: Oldřich Španiel; Czechoslovak exile; anti-nazi resistance; World War II; Czechoslovak Troops; the United States of America; Oldřich Španiel; československý exil, protinacistický odboj; druhá světová válka; československé jednotky v zahraničí; USA